Incorporating Wikis in an Educational Technology Course: Ideas, Reflections and Lessons Learned … - Artino, Anthony R.; Ioannou, Andri (My University, 2009)
The use of wikis in education is a relatively new phenomenon. Although empirical research in this area is limited, wikis appear to be powerful tools, capable of promoting collaboration, knowledge creation and knowledge sharing. This paper outlines how a wiki was used with 24 students enrolled in an Educational Technology introductory course, in an effort to promote collaborative learning and knowledge sharing. Wiki activities are described in sufficient detail to allow new instructors to use them in their courses. Preliminary observations, reflections, and lessons-learned are included.
Keywords: Wikis; Web 2.0